Explaining adoption and use of payment instruments by U.S. consumers - Sergei Koulayev; Marc Rysman; Scott Schuh; Joanna Stavins (Federal Reserve Bank of Boston, 2012)
The way that consumers make payments is changing rapidly and attracts important current policy interest. This paper develops and estimates a structural model of adoption and use of payment instruments by U.S. consumers. We use a cross-section of data from the Survey of Consumer Payment Choice, a new survey of consumer behavior. We evaluate substitution and income effects. Our simulations shed light on the consumer response to the 2011 regulation of interchange fees on debit cards imposed by the Dodd-Frank Act, as well as the proposed settlement between Visa and MasterCard and the Department of Justice that would allow merchants to surcharge the use of payment cards.
Keywords: E41; D41; D12; 330